PHYTOCHEMICAL SCREENING, ANTIOXIDANT, AND CYTOTOXICITY OF Zamioculcas zamiifolia ROOT EXTRACT - Rini Muharini; Masriani Masriani; Rudiyansyah Rudiyansyah (Tanjungpura University, 2018)
Zamioculcas zamiifolia is an ornamental plant that had been used pharmacologycally as a traditional medicine plant. The aims of this research were to investigate the phytochemistry of n-hexane, chloroform and methanol extracts from the roots of Z. zamiifolia and to evaluate their biological activities as antioxidant and cytotoxic. All extracts were screened phytochemically using specific reagents and TLC technique to reveal the major component of each extract. The chloroform was obtained as the highest quantity of extract which gave positive test for steroids and flavonoids. All extracts were tested for their antioxidant activity using DPPH method and for their cytotoxic activity against two types of human cancer cell lines, HepG2 and T47D, and normal African green monkey kidney ephitelial cell lines, Vero. The methanol and chloroform extract exhibited antioxidant activity with AA50 values of 180.0 and 431.5 µg/mL, respectively. Chloroform and methanol extracts showed potencial and moderate cytotoxicity towards T47D cell line with IC50 433.1 and 461.1µg/mL, respectively. None of the extracts was toxic against HepG2 and Vero cell lines.